2008
DOI: 10.2746/042516408x313652
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative morphology of the equine laminar junction in relation to capsule shape in the forehoof of Standardbreds and Thoroughbreds

Abstract: Understanding the biological responses of hoof tissues to stress should add to the ability to prevent lameness involving the hoof and maintain its health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
9
1
1
Order By: Relevance
“…Results yielded new information regarding distribuition of this laminaes in different regions of the hoof in both fore and hindlimbs Stashak & Hood (2005) verified homogeneity in morphology and distribution of primary epidermal laminae around the hoof perimeter. Contrastingly, our results showed that both in forelimbs ( Fig.2A) and hindlimbs (Fig.2B), the region of the hoof toe had a greater concentration of primary epidermal laminae, corroborating the studies of Bowker (2003), Bidwell & Bolker (2006) Lancaster et al (2007) and Thomason et al (2008). Douglas & Thomason (2000) mentioned that the hoof toe is the region with the highest stress between the hoof wall and the distal phalanx, the gradual reduction in density of primary epidermal laminae towards the hoof bulb, as observed in the present study, probably is an adaptive response to different stresses in the several regions, once under physiological situations the force imposed in the quarters region would be lower than required in the hoof toe, as well as the stress related to the hoof bulbs is lower than to the quarters.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Results yielded new information regarding distribuition of this laminaes in different regions of the hoof in both fore and hindlimbs Stashak & Hood (2005) verified homogeneity in morphology and distribution of primary epidermal laminae around the hoof perimeter. Contrastingly, our results showed that both in forelimbs ( Fig.2A) and hindlimbs (Fig.2B), the region of the hoof toe had a greater concentration of primary epidermal laminae, corroborating the studies of Bowker (2003), Bidwell & Bolker (2006) Lancaster et al (2007) and Thomason et al (2008). Douglas & Thomason (2000) mentioned that the hoof toe is the region with the highest stress between the hoof wall and the distal phalanx, the gradual reduction in density of primary epidermal laminae towards the hoof bulb, as observed in the present study, probably is an adaptive response to different stresses in the several regions, once under physiological situations the force imposed in the quarters region would be lower than required in the hoof toe, as well as the stress related to the hoof bulbs is lower than to the quarters.…”
Section: Discussioncontrasting
confidence: 54%
“…Much of the literature consulted (Douglas & Thomason 2000, Thomason et al 2005, Lancaster et al 2007, Thomason et al 2008, Kawasako et al 2009) have analyzed only the forelimbs. Comparing forelimbs and hindlimbs, it was found no significant difference regarding the density of primary epidermal laminae, also observed by Bidwell and Bowker (2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since that increases of bifurcation and of length of primary and secondary epidermal laminae contribute with variations in laminar joint, it is possible to support the idea that the normal laminar apparatus is able to respond to mechanical load (Sarratt & Hood, 2005). Thomason et al (2008) have associated changes in the hoof capsule with changes in the laminar joint, suggesting a remodeling of primary epidermal laminae induced by stress. Thus, the change of one of the components of the hoof capsule alters adjacent structures, once the hoof acts as an integrated unit (Redden 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in laminar morphology found in healthy horses cannot be considered normal or pathological, since it is not known whether these findings represent the normal range or manifestations of subclinical diseases (Lancaster et al 2007). In trotter or English Thoroughbred horses (Thomason et al, 2008), is observed a primary epidermal laminae remodeling, induced by stress, but without a complete characterization of the relationship between stress or strain and remodeling process. Redden (2003) mentioned that the distortion of a component of the hoof capsule changes all other components and adjacent tissues.…”
Section: Introductionmentioning
confidence: 99%